Transformation: the impacts of an intercultural exploration on preservice teachers - Aguilar, Christine June, author; Timpson, William, advisor; Cross, Jennifer, committee member; Kees, Nathalie, committee member; Makela, Carole, committee member (Colorado State University. Libraries, 2013)
This action research study focuses on the impacts of an Intercultural Exploration project on 52 preservice teachers enrolled in sections of Schooling in the United States course at Colorado State University in the School of Education. Goals of the course include the intention that students will exhibit increased multicultural awareness and cross-cultural competence as applied to school settings. To inform the study, a review of the literature on multicultural education, intercultural theory, and transformational learning was conducted. The Intercultural Exploration project provided students the opportunity to explore their biases and areas where they lacked understanding of cultural groups, beliefs, and practices. Students spent four hours in a formal or informal setting focusing on one of their biases or lack of understanding. Students wrote essays to describe why they choose their projects, their feelings before and after the experience, how they developed their beliefs and how the project may impact their future personal and professional behaviors. A five level Transformational Rating was developed to assess student transformation based on reported beliefs before and after the project and predicted future personal and professional behaviors. Using the Transformational Rating Students rated their experience and the instructor/researcher rated each experience based on essay responses. The average rating by the instructor/researcher was 3.71 and the average rating by the students was 3.16, indicating that there was a transformation in at least two areas: beliefs, predictions of personal behavior, and professional behavior. Projects were themed by the instructor/researcher as religion (16), behavior (10), mental/physical status (8), socioeconomic status (5), social groups/organizations (3), sexual orientation (3), careers (3), current issues (2), and ethnicity/culture (2). Reasons students chose their projects were because they wanted to explore their own bias (27) or saw opportunities to learn/understand other perspectives (24). Students reported that their beliefs prior to the project were developed due to upbringing (18), media (11), negative experiences (8) and other (6). As a final step, students presented their projects and were asked to discuss the impacts of presenting to and listening to their peers. Following presentations, students said they felt the impact of sharing the Intercultural Exploration though uncomfortable at times, helped them to further understand and articulate their beliefs, while others felt it was an opportunity for their peers to get to know them better. After listening to their peers present, students expressed they enjoyed listening to the variety of presentations. Students also said they learned from their peers and developed a greater awareness of intercultural issues. Students noted they felt a close connection to their peers and some were surprised at the number of religious focused projects. The majority of students was positively impacted by the Intercultural Exploration and experienced a transformation as measured by pre and post beliefs and predicted future personal and professional behaviors. Students were impacted positively by sharing and listening to the Intercultural Exploration. Additional research could focus on replication of the study in other locations to compare results, variations on the project, and a more detailed Transformational Rating. Observing students in their first teaching assignments and examining long-term impacts might provide information for future training of preservice teachers in multicultural competence.
Keywords: action research; cross-cultural; diverse; intercultural competence; multicultural; transformational learning